Catastrophe Risk Financing in Developing Countries : Principles for Public Intervention - Cummins, J. David; Mahul, Olivier (Washington, DC: World Bank, 2012)
Public intervention in catastrophe insurance markets, supported by the donor community and the World Bank, should be country specific. Low-income countries, where the domestic non-life insurance market is undeveloped, should focus in the short term on the development of sovereign catastrophe insurance solutions and the promotion of public goods related to risk market infrastructure. These countries are usually not mature enough for the promotion of catastrophe insurance pools for private homeowners. Middle-income countries, where the domestic non-life insurance market is more developed, should help the private insurance industry offer market-based catastrophe insurance solutions to homeowners and to small and medium enterprises, including the agricultural sector. This book offers a framework, with lessons drawn from recent experience, guiding principles for public intervention and potential roles for donors and International Financial Institutions (IFIs). These lessons are expected to be used in developing affordable, effective and sustainable country-specific catastrophe insurance programs.